2020
DOI: 10.5296/jei.v6i2.17379
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Prospective Teachers’ Attitudes Towards National Parks and Views on Ecology-Based Environmental Education

Abstract: In this study, it was aimed to determine prospective social studies and elementary education teachers’ attitudes towards national parks and views on ecology-based environmental education. In this study, which was conducted following the stated purpose, an educational practice was carried out in Termessos National Park (Antalya) for two days in 2018 with a total of 26 prospective teachers enrolled at faculty of education at Akdeniz University, of whom 11 from social studies education and 15 from elementary educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Some studies in the literature aimed to emphasize the effectiveness of specific environmental education program (Aksut & Aydin, 2021;Ayaz et al, 2021;Bardecki & McCarthy, 2020;Corpuz et al, 2022;Fettahlioglu, 2018;Hamalosmanoglu et al, 2020;Junkaew et al, 2021;Nogales-Delgado & Encinar Martín, 2019;Sims et al, 2020;Sookngam et al, 2021;Wongchantra et al, 2022aWongchantra et al, , 2022b. While others tried to show a relation between environmental education and other variables (Afacan, 2020;Chen et al, 2020;Demirkaya et al, 2020;Kaya et al, 2021;Kilicoglu, 2021;Onal, 2020;Ongon et al, 2021;Praimee et al, 2022). Finally, a small number of studies were about review studies (Dasdemir, 2018;Tumer, 2021;Ulfah et al, 2020) related to environmental education and trends.…”
Section: Conclusion Discussion and Recommandationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies in the literature aimed to emphasize the effectiveness of specific environmental education program (Aksut & Aydin, 2021;Ayaz et al, 2021;Bardecki & McCarthy, 2020;Corpuz et al, 2022;Fettahlioglu, 2018;Hamalosmanoglu et al, 2020;Junkaew et al, 2021;Nogales-Delgado & Encinar Martín, 2019;Sims et al, 2020;Sookngam et al, 2021;Wongchantra et al, 2022aWongchantra et al, , 2022b. While others tried to show a relation between environmental education and other variables (Afacan, 2020;Chen et al, 2020;Demirkaya et al, 2020;Kaya et al, 2021;Kilicoglu, 2021;Onal, 2020;Ongon et al, 2021;Praimee et al, 2022). Finally, a small number of studies were about review studies (Dasdemir, 2018;Tumer, 2021;Ulfah et al, 2020) related to environmental education and trends.…”
Section: Conclusion Discussion and Recommandationsmentioning
confidence: 99%
“…Particularly, Chen et al (2020) revealed that there are positive correlations between environmental education and learning outcomes, learning outcomes and environmental literacy, and environmental education and environmental literacy. Furthermore, Demirkaya et al (2020) showed that "ecology-based environmental education in national park" positively influenced student teachers' attitude towards national parks and positively influenced their understanding of ecological environmental education.…”
Section: Theme 2 Relation Between Environmental Education and Other V...mentioning
confidence: 99%
“…Recent technological development has increased opportunities to intervene in nature which has become a significant pressure on the environment (Demirkaya, 2020). The natural environment in which all living things live has existed for many years without any problems in living things' interaction.…”
Section: Introductionmentioning
confidence: 99%